Pendidikan Berbasis Multikultural Sebagai Upaya Penguatan Nilai Karakter Siswa di SMA Negeri 5 Kupang - Miranti Badu (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The purpose of this study was to determine multicultural-based education and efforts to strengthen the character values of students at SMA Negeri 5 Kupang. The approach taken was qualitative. The selection of research subjects used purposive sampling technique consisted of teachers and students. Research data were collected through observation, interviews, and documentation. The research data were analyzed using source triangulation, technical triangulation, and time triangulation analysis techniques. This study shows several findings; (1) multicultural-based education is implemented by providing encouragement to students through group work so that students can automatically establish cooperative relationships and mutual respect among themselves, and also implemented through the attitudes and ethics of teachers so that students can imitate the good attitudes and ethics shown by teacher. Students are also taught to always respect and respect each other both between students and students, students with teachers and students with parents. (2) The efforts made in strengthening student character are to encourage students to always be honest, respect each other, be responsible for completing assignments given by the teacher, always show commendable attitudes such as always obeying school rules, respecting older people, and respecting fellow students without looking at ethnic, religious, national and racial differences.